Penciptaan Karya Musik Spiritual Dengan Pendekatan Konsep Tradisi Islam Kesenian Badikia - Wimbrayadi Wimbrayadi; Hengki Armez Hidayat; Irdhan Epria Darma Putra (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2021)
All music products born by people who have Islamic culture are actually rich musical potential to be transformed into new musical works based on spiritual Islam. The cultivation of this musical composition is to realize musical ideas inspired by traditional Islamic art activities that show the spiritual presence in the Minangkabau community, becoming a new musical composition. In education, see the extent to which Islamic culture can be created or developed that is still within the tolerance of society based on aesthetic and spiritual Islamic approaches and knowledge of creation. The research method is carried out with an ethnographic approach, in field work activities studio work is also carried out.